Learning related to the Concept of Science and Technology According to Islam - Susdarwono, Endro Tri (Lia Center of Research and Education, 2025)
This study aims to delineate the concepts of science and technology within Islam through a literature review. Modern humanity demonstrates collective intelligence in the form of science and technology, necessitating a profound understanding of these concepts from an Islamic perspective. The research findings indicate that QS al-Alaq, 96: 1-5 and QS Fushshilat 41: 33 implicitly classify fundamental human knowledge into natural and social sciences (derived from ‘cakrawala’ or ‘afaq), and humanities (derived from ‘self or ‘anfus), which include philosophy, linguistics, logic, and mathematics. Technology in Islam is understood as a human endeavor to channel and disseminate divine grace to all creatures, manifesting human devotion to the Creator.